Churchill the unexpected hero - Addison, Paul, 1943- (Oxford University Press, 2005)
"In this incisive biography, Paul Addison examines both the life of the most iconic figure in twentieth-century Bristish history, and the battle over his reputation, which continues to this day."--Jacket.